Halogenation of A-frame μ-carbido complexes: a diamagnetic rhodium(ii) carbido complex. Issue 56 (11th June 2020) - Barnett, Harrison J.; Hill, Anthony F.
Abstract : Chlorination of the new μ-carbido [Rh2 (μ-C)Cl2 (μ-dppf)2 ] (dppf = 1, 1′-bis(diphenylphosphino)ferrocene) affords the dirhodium(ii ) complex [Rh2 (μ-C)Cl4 (μ-dppf)2 ] the carbido bridge of which can only be adequately described by delocalised bonding. Abstract : The reaction of [Rh2 (μ-C)Cl2 (PPh3 )4 ] with 1, 1′-bis(diphenylphosphino)ferrocene (dppf) affords the μ-carbido complex [Rh2 (μ-C)Cl2 (μ-dppf)2 ] which reacts with PhICl2 to provide a diamagnetic dirhodium(ii ) carbido complex [Rh2 (μ-C)Cl4 (μ-dppf)2 ].